Readmission and mortality after first hospital admission with acute hypercapnic respiratory failure (AHRF) requiring non-invasive ventilation (NIV) - Rebecca D'Cruz,; Harman Saman,; Olliver O'Sullivan,; Norashikin Amran,; Jumaa Bwika,; Ben Beauchamp,; Rahul Mukherjee (European Respiratory Society, 2024)
Introduction: Longer term data on mortality of patients requiring NIV due to AHRF have been reported (Thomas A et al. ERJ 2010; 36:54. 402s). We report 1-year mortality and readmission rates of a cohort of such patients admitted to a respiratory ward-based 11-bedded physiotherapy-led NIV unit in a hospital providing acute medical services to a population of about 450000.